2014
DOI: 10.1021/jm500183r
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent and Selective α3β4 Nicotinic Acetylcholine Receptor Antagonist from an α-Conotoxin Synthetic Combinatorial Library

Abstract: α-Conotoxins are disulfide-rich peptide neurotoxins that selectively inhibit neuronal nicotinic acetylcholine receptors (nAChRs). The α3β4 nAChR subtype has been identified as a novel target for managing nicotine addiction. Using a mixture-based positional-scanning synthetic combinatorial library (PS-SCL) with the α4/4-conotoxin BuIA framework, we discovered a highly potent and selective α3β4 nAChR antagonist. The initial PS-SCL consisted of a total of 113 379 904 sequences that were screened for α3β4 nAChR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 51 publications
(119 reference statements)
0
31
0
Order By: Relevance
“…However, the low potency of AuIB at ␣3␤4 and its off-target effect on Ca v 2.2 channel modulation via GABA B receptor activation has hampered its use in in vivo studies. Recent studies in development of selective and potent ␣3␤4 antagonists led to the discovery and synthesis of two novel ␣-conotoxins: TxID, a novel ␣4/6-conotoxin from Conus textile that potently blocks ␣3␤4 (IC 50 ϭ 12.5 nM) (55) and TP-2212-59, a synthetic analog of ␣4/4-conotoxin BuIA (IC 50 ϭ 2.3 nM) (56). Although both peptides are potent inhibitors of the ␣3␤4 nAChR subtype, TxID also inhibits ␣6/␣3␤4 with only 7.5-fold less potency (IC 50 ϭ 94.1 nM) (55) and the activity of TP-2212-59 at other nAChR subtypes such as ␣6-containing receptors is yet to be tested (56).…”
Section: Discussionmentioning
confidence: 99%
“…However, the low potency of AuIB at ␣3␤4 and its off-target effect on Ca v 2.2 channel modulation via GABA B receptor activation has hampered its use in in vivo studies. Recent studies in development of selective and potent ␣3␤4 antagonists led to the discovery and synthesis of two novel ␣-conotoxins: TxID, a novel ␣4/6-conotoxin from Conus textile that potently blocks ␣3␤4 (IC 50 ϭ 12.5 nM) (55) and TP-2212-59, a synthetic analog of ␣4/4-conotoxin BuIA (IC 50 ϭ 2.3 nM) (56). Although both peptides are potent inhibitors of the ␣3␤4 nAChR subtype, TxID also inhibits ␣6/␣3␤4 with only 7.5-fold less potency (IC 50 ϭ 94.1 nM) (55) and the activity of TP-2212-59 at other nAChR subtypes such as ␣6-containing receptors is yet to be tested (56).…”
Section: Discussionmentioning
confidence: 99%
“…A synthetic combinatorial library derived from α‐conotoxin BuIA sequence revealed 11 analogues with inhibitory activity at the α3β4 nAChR. One of these analogues, termed TP‐2212‐59, is one of the most potent and selective α3β4 antagonists known to date, with a calculated IC 50 of 2.3 nM at α3β4 and more than 1000‐fold less activity at α3β2 and α7 subtypes (Chang et al, ).…”
Section: Designing α‐Conotoxin Analogues To Improve Nachr Subtype Selmentioning
confidence: 99%
“…To broaden our understanding of nAChR pharmacology, we used α-conotoxin LsIA to identify the minimum structural requirements for α-conotoxin activity at human α3β4 nAChR. Native LsIA is an equipotent antagonist of the human α7 and rat α3β2 but inactive at α3β4 nAChRs 23 despite relatively high sequence identity to α-conotoxins with activity at the α3β4 nAChRs 23 24 25 26 27 28 29 30 31 32 ( Table 1 ). Using a co-crystal structure of LsIA and Lymnaea stagnalis acetylcholine binding protein (AChBP) to guide mutational studies, we identified that LsIA arginine at position 10 (R10) and asparagine at position 12 (N12) determined LsIA inactivity at α3β4.…”
mentioning
confidence: 99%